Twenty-five years of French jurisprudence in criminal medical liability. (January 2018) - Faisant, Maxime; Papin-Lefebvre, Frédérique; Rerolle, Camille; Saint-Martin, Pauline; Rougé-Maillart, Clotilde
We report on a comprehensive 25-year study on criminal medical liability in France, undertaken to establish trends in the number of cases being brought before the criminal courts. We did this by interrogating the database on the Légifrance website using a Boolean equation (' pénal ' (criminal) AND ' médecin ' (physician) OR ' docteur ' (doctor)). In total 539 cases were selected, in which the status of the physician either influenced the punishment imposed, or was a prerequisite for the commission of the offence. The results of the search produced two outcomes: offences and the dates of the most recent criminal judgements (which had been left blank). Further data were also collected: references to court cases, hearing dates, offence dates, procedural time limits, numbers of accused parties, types of punishments and physician characteristics. The number of court hearings increased from the 1980s until the late 1990s. Since then, it has remained stable at around 25 cases per year. Of the defendants appearing before the courts, 39.2% have been found guilty. On average, 10 to 13 physicians every year – that is, one per month – are punished. Those most often punished are obstetrician-gynaecologists (13%), followed by intensive care anaesthetists (11%) and then by general practitioners (6.7%). The offences most frequently occurring are manslaughter (36.5%), illegal profits (12%), unintentional injuries (11.5%) and sexual offences (10.1%). The results are most reassuring in terms of the risks posed by the practice of medicine in France. Such a risk does indeed exist; however, it is at a low level and stable.